The Effectiveness of Comic Illustrated Augmented Reality Learning Media to Improve Mathematical Problem-Solving Ability - Ivana; Pramudya, Ikrar; Riyadi (Universitas Pendidikan Ganesha, 2023)
Problem solving is an interaction between knowledge that uses cognitive and affective thinking processes. However, currently the PISA results show that students' mathematical problem-solving abilities in Indonesia are still low. One of the new lessons that is currently being developed is the use of augmented reality technology. The aim of this research is to develop comic illustrated augmented reality learning media to improve mathematical problem-solving abilities. The type of research used is R & D (Research & Development) research. The ADDIE model used in this research consists of analysis, design, development, implementation, and evaluation. The data analysed were obtained from pretest and post-test. There were 31 students in the experimental class and 30 students in the control class. The results of the mean difference hypothesis test for effectiveness data produced t-obs = 9.26 with a critical area (t>1,6973) so that the test decision was that H0 was rejected. So, it can be concluded that augmented reality learning media with comic illustrations is effective in improving middle school students' problem-solving abilities.